DNA sequence analysis : hypercomplex number representation, statistical properties of CIS-regulatory region - Li, Ya Jing (2009)
Automated analysis of genomic data is a crucial problem in post-sequencing genome era. In this thesis, we focus on exploring computational method to identify cisregulatory regions automatically.